Measurements of Soil Carbon Dioxide Emissions from Two Maize Agroecosystems at Harvest under Different Tillage Conditions - Gerosa Giacomo; Finco Angelo; Boschetti Fabio; Brenna Stefano; Marzuoli Riccardo (The Scientific World Journal)
In this study a comparison of the soil CO2 fluxes emitted from two maize (Zea mays L.) fields with the same soil type was performed. Each field was treated with a different tillage technique: conventional tillage (30 cm depth ploughing) and no-tillage. Measurements were performed in the Po Valley (Italy) from September to October 2012, covering both pre- and postharvesting conditions, by means of two identical systems based on automatic static soil chambers. Main results show that no-tillage technique caused higher CO2 emissions than conventional tillage (on average 2.78 and 0.79 μmol CO2 m−2 s−1, resp.). This result is likely due to decomposition of the organic litter left on the ground of the no-tillage site and thus to an increased microbial and invertebrate respiration. On the other hand, fuel consumption of conventional tillage technique is greater than no-tillage consumptions. For these reasons this result cannot be taken as general. More investigations are needed to take into account all the emissions related to the field management cycle.